Selective feeding of three bivalve species on the phytoplankton community in a marine pond revealed by high-throughput sequencing - Ling Qiao; Zhiqiang Chang; Jian Li; Tiejun Li (Scientific Reports, 2022)
Abstract The study of the selective feeding of bivalves is necessary in order to improve our understanding of bivalve growth and development, which helps to better define the roles of bivalves in their ecosystems. Little information is currently available on the feeding preferences of bivalves in natural waters, since all diets are provided as single or mixed algae in experiments. In this study, high-throughput sequencing of the 23S rRNA gene was performed to explore differences in the feeding selectivity of Mercenaria mercenaria, Meretrix meretrix and Ruditapes philippinarum during different stages of their culturing to reveal their feeding preferences in natural waters. We found that the three bivalve species had different preferential selection of phytoplankton genera, indicating specific selection and avoidance of particular types of algae during their development in aquaculture. M. mercenaria was the most selective of the bivalves, followed by M. meretrix and then R. philippinarum. With the growth of M. mercenaria and M. meretrix, more kinds of phytoplankton could be ingested. In addition, high-throughput sequencing showed that some picophytoplankton including Synechococcus, Microchloropsis, and Chrysochromulina were dominant in the hepatopancreas samples obtained from these three bivalves. Therefore, the importance of these pico-sized algae in bivalve diets should be reassessed.